2017
DOI: 10.1364/ol.42.002854
|View full text |Cite
|
Sign up to set email alerts
|

Tunable coupling-induced resonance splitting in a self-coupled silicon ring cavity with robust spectral characteristics

Abstract: We propose and demonstrate a self-coupled micro ring resonator for resonance splitting by mutual mode coupling of cavity mode and counter-propagating mode in Silicon-on-Insulator platform The resonator is constructed with a self-coupling region that can excite counter-propagating mode. We experimentally study the effect of selfcoupling on the resonance splitting, resonance extinction, and quality-factor evolution and stability. Based on the coupling, we achieve 72% of FSR splitting for a cavity with FSR 2.1 nm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…We have earlier shown that splitting the resonances is a potential solution where a cavity resonance could be selectively splitted into closely spaced reconences [17]. Such splitting of resonances have already been demonstrated and utilized in areas like photonic links [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have earlier shown that splitting the resonances is a potential solution where a cavity resonance could be selectively splitted into closely spaced reconences [17]. Such splitting of resonances have already been demonstrated and utilized in areas like photonic links [18].…”
mentioning
confidence: 99%
“…It is an assembly of a conventional MRR externally loaded with a Self−Coupled MRR (SCMRR). A detailed discussion on the design and working principle of the SCMRR is presented in ref [17]. A typical MRR has mode propagating in either clockwise or anti-clockwise direction and resonates at wavelengths that phase match with the cavity.…”
mentioning
confidence: 99%